2020
DOI: 10.21203/rs.3.rs-51714/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Feeding malic acid to chickens at slaughter age benefits poultry production and microbial safety in regard to Campylobacter

Abstract: Background Chicken meat has become popular for consumption worldwide. However, chicken flocks suffer the Campylobacter infection during the rearing period, which allows chicken meat products act as a vehicle for transmitting this pathogen through the food chain and bring great health and economic burden to the public. Malic acid is a dicarboxylic organic acid with antimicrobial activity, the application of malic acid during food animal rearing period also found could improve the performance of animals and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 33 publications
(52 reference statements)
0
4
0
Order By: Relevance
“…Supplementation with malic acid via drinking water for broiler chickens suffering from respiratory diseases showed a surprising result, improving survival rates by 20% in the treated group compared to the control group (REN et al, 2020).…”
Section: Malic Acidmentioning
confidence: 96%
See 3 more Smart Citations
“…Supplementation with malic acid via drinking water for broiler chickens suffering from respiratory diseases showed a surprising result, improving survival rates by 20% in the treated group compared to the control group (REN et al, 2020).…”
Section: Malic Acidmentioning
confidence: 96%
“…Even malic acid (5 and 10%) proved to be efficient in preventing biofilm by Salmonella enteritidis at 12°C (MENEZES; MORAES, 2017). Ren et al (2020) observed that drinking water supplemented with malic acid for five days for slaughter-age birds reduced Campylobacter excretion by 1.05-1.55 log, suggesting that there is an effective reducing effect on the excretion of microorganism. Malic acid had no adverse effects on broiler performance, including body weight, intestinal indices, and intestinal microflora.…”
Section: Malic Acidmentioning
confidence: 98%
See 2 more Smart Citations